Advertising strategies in Television Malaysia's advertisements - Vasudevan, Chellammal (Universiti Sains Malaysia, 1982)
This is a study to find out about advertising strategies is our local advertisements.Advertisement,as we know,are part and parcel life,we are bombarded with advertisements every where we go